Transcription and methylation of flax rDNA. - Ellis, T H (1983)
The transcription of flax rDNA and the processing of the rRNA precursors is described. The location of methylated regions of the rDNA has been assayed, one of the least methylated regions maps close to the 5' end of the largest identified rRNA precursor.